Endogenous Enzyme-responsive Nanoplatforms for Anti-tumor Therapy - Lou, Xue-Fang; Du, Yong-Zhong; Xu, Xiao-Ling (Current Drug Targets, 2021)
The emergency of responsive drug delivery systems has contributed to reduced cytotoxicity, improved permeability in tissues and extended circulation time of the active drug. In particular, enzyme-responsive nanoplatforms have attracted a lot of attention due to the specificity and efficiency of an enzyme-catalyzed reaction. In this review, enzyme-based mono responsive drug delivery systems designed in the past 5 years have been summarized. These drug delivery systems were introduced by different tumor-related enzymes such as matrix metalloproteinase, esterase, hyaluronidase, caspase and cathepsin. Moreover, the enzyme-sensitive nanoplatforms activated by dual-stimuli have been also described. Although great progress had been made in the past years, the translation into clinical practice is still difficult. Thus, three obstacles (enzyme heterogeneity, reaction environment, animal model) were also discussed. In short, enzyme-activated drug delivery systems offer great potential in treating cancers.
Keywords: caspase